2018
DOI: 10.1111/tops.12359
|View full text |Cite
|
Sign up to set email alerts
|

Communication in Theory and Research on Transactive Memory Systems: A Literature Review

Abstract: Transactive memory systems (TMS) theory has attracted considerable attention in the scholarly fields of cognitive, organizational, and social psychology; communication; information science; and management. A central theme underlying and connecting these scholarly fields has been the role of interpersonal communication in explaining how members of dyads, groups, and teams learn "who knows what," specialize in different information domains, and retrieve information from domain experts. However, because theoretic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 67 publications
1
29
0
Order By: Relevance
“…In our review, we identified six topics worthy of future research on communication and TMS: (1) the role of technology; 2) member roles and characteristics; (3) non-task and nonverbal communication (i.e., facial expression, emotional/relational interaction); (4) communication and TMS structures, (5) group context, and (6) TMS errors. In their review, Peltokorpi and Hood (2018, p. 18) identified five additional and more specific future research directions on this topic: (1) combined effects of communication frequency and quality over time; (2) the impact of frequency of communication on expert inferences; (3) the effects of task, relationship and process conflict on TMS-related communication; (4) the impact of language and cultural differences on TMS-related communication; and (5) the impact of network size on TMS-related communication. In the following sections, we discuss each of the six topics identified above in more detail and then advocate for a multidimensional network perspective that can address many of these topics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our review, we identified six topics worthy of future research on communication and TMS: (1) the role of technology; 2) member roles and characteristics; (3) non-task and nonverbal communication (i.e., facial expression, emotional/relational interaction); (4) communication and TMS structures, (5) group context, and (6) TMS errors. In their review, Peltokorpi and Hood (2018, p. 18) identified five additional and more specific future research directions on this topic: (1) combined effects of communication frequency and quality over time; (2) the impact of frequency of communication on expert inferences; (3) the effects of task, relationship and process conflict on TMS-related communication; (4) the impact of language and cultural differences on TMS-related communication; and (5) the impact of network size on TMS-related communication. In the following sections, we discuss each of the six topics identified above in more detail and then advocate for a multidimensional network perspective that can address many of these topics.…”
Section: Discussionmentioning
confidence: 99%
“…There are previous reviews of TMS research where communication was not a central focus (see Hollingshead et al, 2012; Lewis & Herndon, 2011; Ren & Argote, 2011). Most recently, Peltokorpi and Hood (2018) published a review of 20 theoretical papers and 34 empirical studies on this topic. Their summarized findings and critique were organized around four topic areas: communication frequency and quality, communication medium and group development, communication styles, and communication networks.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Communication is what makes TMSs truly transactive (see Peltokorpi & Hood, ; for a review in this topic). Research has shown how communication frequency and quality (Jackson & Moreland, ; Peltokorpi & Manka, ), communication medium (Hollingshead, ), communication styles (Yoon & Hollingshead, ), and communication networks (Palazzolo, ) affect the formation, development, and effectiveness of TMSs over time.…”
Section: Conversational Dynamicsmentioning
confidence: 99%
“…The contributions of Harris, Barnier, Sutton, and Savage (), Peltokorpi and Hood (2018), and Rajaram and Maswood (2018) all present interesting and important aspects of the ways in which conversations shape the way individuals and groups remember the past. At the same time, we think that the presented work suggests several possible expansions or revisions of both methodological and theoretical aspects.…”
mentioning
confidence: 99%